Comparison of lead and cadmium chloride poisoning on bovine haemoglobin - Noor Azlan, Najihah; Othman, Siti Amira (Penerbit UTHM, 2020)
In our earth, the metallic element is naturally occurring and used in occupational, industrial and environmental area. Heavy metal is a metal that has high level of toxicity that can affect human health. The toxicity of metal can be exposed to human through a chemical process, physical process, food chain, water and soil. In this research, Cadmium chloride and lead were used. These two materials have been used widely in daily life. This research is mainly to study the effect of lead and cadmium chloride contamination with blood. The aspect of pH is also studied in this research. The effects of lead and cadmium chloride to human blood is tested using blood sample obtained from a haemoglobin bovine blood. Different amount of lead and cadmium chloride are dissolved in the blood sample to compare the level of concentration of lead and cadmium in the blood. The morphology of the blood between different concentrations of lead cadmium in blood was also observed. The morphology of the blood was obtained through FESEM and compared with the normal blood. The morphology of blood was change when lead and cadmium chloride was added and it affects the functionality of the blood.